Overview of the development of satellite navigation blanket interference monitoring - He, Yinhui; Li, Baiyu; Chen, Jinping; Wang, Zhi; Xiao, Wei; Lu, Zukun (Frontiers in Physics, 2024)
Satellite navigation interference monitoring is an important means to effectively evaluate interference and ensure the normal operation of global navigation satellite system (GNSS). Once interference is detected, this monitoring can identify the type of it, perform direction-finding and localization, evaluate its impact on GNSS, and guide the implementation of effective countermeasures. With the continuous progress of interference technology, the power required to cause the same jamming effect to the navigation system is getting smaller and smaller. Traditional radio monitoring system has been unable to meet the needs of the current satellite navigation monitoring in terms of sensitivity and accuracy. It is of great significance to develop and improve the dedicated satellite navigation monitoring system. This paper introduces the basic concept of satellite navigation interference monitoring and the composition of the system, analyzes the key technologies and finally gives an outlook on the development trends in this field.